Synthesis and Physicochemical Characterization of Chitin Derivatives - İlhan Uzun; Giray Topal (Journal of Chemistry)
Firstly, chitin derivatives were synthesized. For this purpose, chitin was modified via ring-opening reaction with cyclic anhydrides in lithium chloride/N,N-dimethylacetamide. Then, chitin derivatives synthesized were characterized by FTIR, 1H NMR, 13C NMR, and U-Vis spectroscopies and scanning electron microscopy. Thermogravimetric analysis was performed to investigate the thermal stability of chitin derivatives. Thermogravimetric analysis results showed that chitin modified with trimellitic anhydride is thermally more stable than chitin modified with phthalic anhydride. In addition, the electrical conductivity of chitin modified with phthalic anhydride and trimellitic anhydride was also measured. Electrical conductivity measurement results showed that the electrical conductivity of chitin modified with trimellitic anhydride (1.2×10−4 S cm−1) is higher than that of chitin modified with phthalic anhydride (9.2×10−5 S cm−1).